Optimising metallic coatings strategies for enhanced surface performance of bioresorbable polymeric stents - Ana M. Sousa; Ana M. Amaro; Ana P. Piedade (Applied Surface Science Advances)
Atherosclerosis remains a prevalent global disease, with coronary stents serving as a key treatment avenue. However, challenges persist, including issues of cellular compatibility, mechanical strength, and degradation rates across stent types. Polymeric Bioresorbable Stents (BRS) have shown promising results in solving some of these problems. However, enhancing their mechanical performance and surface characteristics is imperative.Metallisation of polymeric parts has been indicated as a solution to improve the mechanical and surface performance of medical devices. This study explores the possibility of using metallic coatings deposited via non-reactive radiofrequency (rf) magnetron sputtering to increase the functionality of BRS. The metallic coatings were of biodegradable metals within the logic of a biodegradable invasive overall stent. Thus, the main objective of this research was to optimise the deposition parameters and evaluate the properties and characteristics of pure magnesium (Mg) and zinc (Zn) coatings. The films were characterised by their structural, morphological, mechanical, and surface performance. The in vitro tests included the study of the degradation kinetics in simulated blood plasma (SBP). The influence of the surface modification of a polymeric coronary stent, both during and post-placement, was evaluated through finite element analysis (FEA) and compared with the pristine polymer.The results revealed that Mg coatings deposited at higher pressure exhibited lower mechanical properties and faster degradation behaviour, albeit with greater thickness and reduced water reactivity. Nevertheless, increasing the pressure reduces the probability of thrombus formation, making it suitable for use in Mg coatings. Conversely, Zn coatings deposited at lower pressure showcased favourable mechanical properties, thickness, and morphology, with minimal blood coagulation risk and comparable water reactivity to thin films deposited at higher pressure. The in silico outcomes of the coated stents showed that the elastic recoil observed after stent placement was reduced for the coated polymeric stents, resulting in recoil ratios comparable to those of permanent metallic structures made with CoCr. Overall, Zn films, particularly those produced at 0.4 Pa, emerge as optimal coatings for coronary stents, considering the results of the thorough experimental and numerical simulation characterisations.